100,000 and Under Occupational Education in the Rural Community Junior College - Hall, George L.; American Association of Junior Colleges ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
Young people move from rural to urban areas for lack of educational and employment opportunity. Nonurban junior colleges, by correcting these lacks, may help to stem this migration--in spite of a shortabe of faculty, funds, and space. Among their unique problems are: (1) the region often depends on a single industry; (2) students must travel farther to school or pay for housing; (3) with less vocational guidance, students are unaware of broader opportunities; (4) faculty is hard to hire because of lower pay and distance from city amenities; (5) families have little income and less interest in continuing education; (6) the area has a meager tax base. These factors combine to limit the comprehensiveness of the rural college. Of the 600 rural colleges, 40% are in population centers of 10,000 or less, with limited chances for employment. Transfer programs vary little; enrollment in agriculture and natural resources is growing; the most popular courses are business, physical science, health, trades, and industry. This report discusses the importance of lay advisory committees (general and occupational), to develop community interest and emphasizes the necessity for more counseling in the choice of an occupation and its course requirements. The college's community services must include not only the usual culture and recreation programs, but also such less common services as soil analysis and commercial consultation help. The rural college needs more research on student characteristics and its own unique role, according to its resources. (HH)
Availability: American Association of Junior Colleges, 1315 Sixteenth Street, N.W., Washington, D.C. 20036 ($1.50).
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Rural Environment; Rural Urban Differences; Rural Education; Two Year Colleges